Multiple Intelligences as an Opportunity for Differentiated Learning - Turcan, Lilia; Bîrsan , Elena (Didactica Danubiensis, 2025)
Objectives: This study analyzes the concept of intelligence as an expression of the higher-order organization of all human psychological processes, and views multiple intelligences as an opportunity for differentiated learning. Previous work: The research revisits contemporary studies on multiple intelligences and emphasizes their potential to support the personalization and differentiation of the learning process. Approach: The scientific foundation of this study is grounded in a detailed analysis of the spectrum of intelligences, highlighting the specific advantages and limitations inherent to each type. Results: The study highlights the distinct characteristics of multiple intelligences and emphasizes the importance of identifying and cultivating individual strengths, while recognizing the diversity of skills and talents innate to each individual. Implications: The research presents arguments supporting the relevance of multiple intelligences within the context of differentiated learning and emphasizes the essential role of teachers in diversifying pedagogical strategies to foster the development of various types of intelligence among students. Research value: The study contributes to clarifying the concept of multiple intelligences by highlighting its significance for self-awareness and personal development, while simultaneously demonstrating the importance of recognizing all forms of intelligence and maximizing each individual’s potential to facilitate their professional and social inclusion